KNOWLEDGE, ATTITUDE, AND PRACTICES OF UNDERGRADUATE MEDICAL STUDENTS REGARDING THE USE OF SOCIAL MEDIA FOR EDUCATIONAL PURPOSES: A CROSSSECTIONAL, OBSERVATIONAL STUDY IN A TERTIARY CARE MEDICAL INSTITUTION IN THE EASTERN ZONE OF INDIA - AGNIDIPA SANYAMATH,; SUHENA SARKAR,; MANAB NANDY,; SHRITAMA BANERJEE,; BIRUPAKSHA BISWAS, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of the study was to seek knowledge, attitude, and practice of medical students toward the use of social media for their educational purposes. Materials and Methods: A questionnaire-based study has been conducted among undergraduate medical students in Medical College, Kolkata. A pre-structured questionnaire was circulated among the students and they were asked to fill it. Results: A total of 275 medical students were included in the study. Almost all the students (98.9%) were aware of social media. The frequency of using social media is seen multiple times in 66.5% of respondents and about 27.6% used social media once or twice daily. Around 42.5% of the students acknowledged that social media has helped them in improving regarding their academic performance, whereas the rest disagreed with it. Most of the students (66.9%) have agreed that social media have made their learning more interesting and simplified, thereby contributing to their educational purposes. Conclusion: We conclude from our study that the medical students informed that social media is an essential tool for acquiring information. Medical students informed that they use social media not only to amass knowledge but to improve their interprofessional communication as well.